DESIDERATA FOR LINGUISTIC SOFTWARE DESIGN - Garretson, Gregory (International Journal of English Studies, 2008)
This article presents a series of guidelines both for researchers in search of software to be used in linguistic analysis and for programmers designing such software. A description of the intended audience and the types of software under consideration and a review of some relevant literature are followed by a discussion of several important considerations in evaluations of a project’s software requirements. The main section of the article then presents a series of guidelines or desiderata, grouped thematically, for the design of software for linguistic analysis. These describe goals and principles of interest both to programmers designing software and to researchers deciding on requirements or evaluating tools. The article closes with an exhortation to researchers and developers to communicate closely during the software design process and to understand the compromises that are necessary.